2009
DOI: 10.1016/j.ygyno.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase III trial in advanced endometrial carcinoma of surgery and volume directed radiation followed by cisplatin and doxorubicin with or without paclitaxel: A Gynecologic Oncology Group study

Abstract: Objectives After surgical debulking and volume-directed irradiation of the pelvis/para-aortic lymph nodes, treatment was randomized to compare recurrence-free survival (RFS) and toxicity between two chemotherapy regimens for the treatment of women with advanced stage endometrial carcinoma. Methods Treatment was randomized between 6 cycles of cisplatin [C] (50 mg/m2) and doxorubicin [D] (45 mg/m2) with or without paclitaxel [P] (160 mg/m2). Initially in paclitaxel treated patients and, after May 2002, all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 24 publications
7
130
0
2
Order By: Relevance
“…Even in patients with minimal residual disease, such as those treated on Gynecologic Oncology Group protocols 122 and 184, the recurrence rate still approaches 50%. 2,24 As a result, a sizable population exists for whom active second-line therapy is needed. How to best treat this population is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients with minimal residual disease, such as those treated on Gynecologic Oncology Group protocols 122 and 184, the recurrence rate still approaches 50%. 2,24 As a result, a sizable population exists for whom active second-line therapy is needed. How to best treat this population is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no specific tailored treatment exists for relapsed type II endometrial cancer due to the rarity of this disease. Still, the current gold standard treatment for relapsed type II endometrial cancer is the same as that for relapsed type I endometrial cancer, which is based on a series of published phase III randomized trials that focused on the efficacy of chemotherapy (7,(21)(22)(23)(24)(25). However, given the apparent differences in clinical behavior between type I and type II endometrial cancers, it has been suggested that treatments should be tailored according to the histologic type.…”
Section: Discussionmentioning
confidence: 99%
“…1 The GOG Corpus Committee is charged with the responsibility of protocol development for advanced endometrial carcinoma. The statistical updates contained in the six month statistical reports, now readily available on the GOG web site, are reviewed at each six month meeting.…”
Section: Challenges Derived From Gog184 For Future Consideration?mentioning
confidence: 99%
“…Stage (IV vs III), residual disease (gross vs microscopic), extended field radiation (yes vs no), histology/grade (serous vs adenocarcinoma), positive para-aortic node (yes vs no), positive cytology (yes vs no), pelvic metastases (serosa/adnexa yes or no) and age (risk increases with age) were significantly associated with RFS with the most high risk categories of clear cell/papillary serous histology and grade 3 adenocarcinoma. 1 Or should GOG184R be a duplicate ten year trial with different chemotherapy in the exact same population? 11.…”
Section: Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation